2018
DOI: 10.5209/reciem.59576
|View full text |Cite
|
Sign up to set email alerts
|

Problemas técnicos en iniciación al violín: un estudio exploratorio en el aula con alumnos preescolares de 4 y 5 años

Abstract: Resumen. Conocer los errores técnicos de los alumnos en la enseñanza de la música puede ser de gran ayuda en la planificación de la enseñanza instrumental en sus fases iniciales. Esto es particularmente valioso en el trabajo con alumnado de 4-5 años. Este estudio explora esta cuestión mediante una Investigación-Acción realizada con 11 estudiantes voluntarios de dichas edades. A lo largo de 30 sesiones individuales de 30 minutos, se recogieron datos mediante observación participante realizada por el profesor en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…This pattern coincides with the D major scale, which has been considered by pedagogue and violinist Joseph Joachim to encourage the natural position of the LH fingers on the violin fingerboard (Yampolsky, 1967). As previously stated, this spacing is very relevant in violin initiation, since it represents one of the typical problems of the LH (Hamann & Gillespie, 2004; Macián-González & Tejada, 2018). However, the order of pitches presentation can be different in the same teaching approach (Macián-González & Tejada, 2020).…”
Section: Learning Intonation On Violin and Violamentioning
confidence: 87%
See 2 more Smart Citations
“…This pattern coincides with the D major scale, which has been considered by pedagogue and violinist Joseph Joachim to encourage the natural position of the LH fingers on the violin fingerboard (Yampolsky, 1967). As previously stated, this spacing is very relevant in violin initiation, since it represents one of the typical problems of the LH (Hamann & Gillespie, 2004; Macián-González & Tejada, 2018). However, the order of pitches presentation can be different in the same teaching approach (Macián-González & Tejada, 2020).…”
Section: Learning Intonation On Violin and Violamentioning
confidence: 87%
“…Finally, the effects of the teaching approach in initial violin lessons were addressed by Macián-González and Tejada (2018) in an intervention-based study involving 11 preschoolers aged 4-5 years in two different groups. One group started studying with the right hand (RH) and then included the LH.…”
Section: Learning Intonation On Violin and Violamentioning
confidence: 99%
See 1 more Smart Citation
“…Between the ages of 5 and 7, approximately half of all children still exhibit excessive flexion of the index finger when using a pencil (Payne & Isaacs, 2016). In bow holds, flexion of fingers is an often observed problem among 4- and 5-year-old children (Macián-González & Tejada Giménez, 2018).…”
Section: Grip Patterns In Bow-hold Developmentmentioning
confidence: 99%
“…While the left hand performs intricate finger-stopping movements, the right-hand fingers ideally should not mirror these movements while bowing. Macián-Gonzáles and Tejada Giménez (2018) observed that 4- and 5-year-old violinists inadvertently moved the fingers of both hands when trying to play their instrument. This added challenge of inhibiting involuntary movement in addition to performing appropriate movement sequences makes the asymmetrical motor requirements of playing the violin difficult to execute for young children.…”
Section: Effects Of Overflow On Bimanual Coordinationmentioning
confidence: 99%